2002
DOI: 10.3732/ajb.89.8.1229
|View full text |Cite
|
Sign up to set email alerts
|

Landscape‐level spatial genetic structure in Quercus acutissima (Fagaceae)

Abstract: Quercus acutissima (Fagaceae), a deciduous broad-leaved tree, is an important forest element in hillsides of South Korea. We used allozyme loci, Wright's F statistics, and multilocus spatial autocorrelation statistics to examine the distribution of genetic diversity within and among three local populations and the spatial genetic structure at a landscape scale (15 ha, 250 × 600 m) on Oenaro Island, South Korea. Levels of genetic diversity in Q. acutissima populations were comparable to mean values for other oa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 82 publications
0
28
1
3
Order By: Relevance
“…The level of polymorphism detected (an average of 20 alleles per locus and heterozygosity of 0.820 for the whole species) is almost equal to the values observed in other Quercus species based on microsatellite loci and similar sample sizes, e.g., Q. petraea (Streiff et al 1998), Q. petraea (Cottrell et al 2003), and Q. lobata (Dutech et al 2005). The discovery of the average observed heterozygosity being slightly, although not significantly, lower than expected heterozygosity (mean F IS = 0.136) within natural populations of Q. aquifolioides, is similar to that detected in other oak species (Guttman and Weigt 1989, Schnabel and Hamrick 1990, Berg and Hamrick 1993, Chung et al 2002. However, the F IS values were found to vary a great deal across loci (-0.548 to +0.76).…”
Section: Discussionmentioning
confidence: 83%
“…The level of polymorphism detected (an average of 20 alleles per locus and heterozygosity of 0.820 for the whole species) is almost equal to the values observed in other Quercus species based on microsatellite loci and similar sample sizes, e.g., Q. petraea (Streiff et al 1998), Q. petraea (Cottrell et al 2003), and Q. lobata (Dutech et al 2005). The discovery of the average observed heterozygosity being slightly, although not significantly, lower than expected heterozygosity (mean F IS = 0.136) within natural populations of Q. aquifolioides, is similar to that detected in other oak species (Guttman and Weigt 1989, Schnabel and Hamrick 1990, Berg and Hamrick 1993, Chung et al 2002. However, the F IS values were found to vary a great deal across loci (-0.548 to +0.76).…”
Section: Discussionmentioning
confidence: 83%
“…The spatial distributions of allozyme polymorphisms were analyzed separately for age classes I through VII using both Moran's Istatistics (Sokal and Oden 1978) and a pairwise estimate of genetic correlation, f ij (''coancestry'' coefficient; sensu Kalisz et al 2001), which measures the correlation between the frequency of a random allele from one individual with that of a random allele from another (Cockerham 1969). f ij has been used in a number of recent studies (e.g., Loiselle et al 1995 Kalisz et al 2001;Parker et al 2001;Chung et al 2002;Chung et al 2003). Values of I-statistics averaged over alleles allowed indirect estimation of Wright's (1943) neighborhood size (Epperson and Li 1996;Epperson et al 1999;Chung and Epperson 1999;Epperson and Chung 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Katsvanga et al (2007) have also reported high variability in fruit traits among sites largely attributed to climatic, edaphic, genetic, and cultural factors. The extent to which individuals develop within the species is also a function of the mechanism of seed dispersal (Chung et al 2002). In addition, management regimes within a given environment may also cause morphological variation especially for traits targeted by artificial selection (Carmona and Casas 2005).…”
mentioning
confidence: 99%